Penyelesaian Sengketa Batas Tanah Melalui Peradilan Adat (Studi di Gampong Ujong Lamie dan Alue Seupeng Kabupaten Nagan Raya) (Sekolah Tinggi Agama Islam Negeri (STAIN) Teungku Dirundeng Meulaboh Aceh Barat, 2017)
Land issues are a matter related to basic people's rights so that land is often contested by everyone. The complexity of land disputes is a result of land requirements, disputes can occur vertically, horizontally or vertically-horizontally. Land disputes should not always be resolved through court but they can also be resolved through out-court channels such as customary justice with the aim of avoiding ongoing dispute. Customary courts are given the authority to resolve land boundary disputes with the principle of familial approach. Settlement of land boundaries through customary courts can be done by means of mediation, deliberation and negotiation to obtain a peaceful collective agreement. In the results of the research note that the existence of land boundary disputes successfully resolved peacefully through customary court. The dispute was in Gampong Ujong Lamie and Alue Seupeng of Nagan Raya District. By looking at the settlement process practiced by this customary court, it has been shown that customary judicial institutions have already demonstrated their role and existence in settling land boundary disputes.